Clinical, neurological, laboratory and neuropsychological features of the course of cerebrovascular diseases in patients infected with SARS-CoV-2 - Marshtupa, V.V.; Nasonova, T.I. (Medicni Perspektivi, 2023)
The rapid global spread of the COVID-19 virus has caused an unprecedented pandemic, in the conditions of which a significant number of pathological consequences of this disease have appeared. In particular, COVID-19 affected the course of cerebrovascular disease, the consequences of which cause disorders of the normal functioning of the brain. Therefore, the aim of the study was to improve the diagnosis of cerebrovascular disease in patients infected with SARS-CoV-2 by studying clinical, neurological, laboratory and neuropsychological indicators. The trial uses Beck’s Anxiety Inventory, Hamilton Depression Rating Scale; neuropsychological tests – Mina Mental State Examination, Montreal Cognitive Assessment; clinical – neurological status; laboratory – complete blood count, erythrocyte sedimentation rate), C-reactive protein, D-dimer, indicators of the blood coagulation system, procalcitonin; polymerase chain reaction, a test for the detection of ribonucleic acid of the COVID-19 virus; statistical. The revealed results indicate deviations from the norm of most indicators in patients infected with SARS-CoV-2 in particular such as leukocytes (t=3.18, p≤0.01), lymphocytes (t=3.83, p≤0.01), band neutrophils (t=2.33, p≤0.05), segmented neutrophils (t=2.29, p≤0.05), erythrocyte sedimentation rate (t=2.17, p≤0.05), platelets (t =2.86, p≤0.01), prothrombin index (t=3.17, p≤0.01), D-dimer (t=2.11, p≤0.05), fibrinogen (t=2 .53, p≤0.05), C-reactive protein (t=2.97, p≤0.01), procalcitonin (t=2.64, p≤0.05). Patients with a history of SARS-CoV-2 had significantly lower indicators of cognitive (t=-2.17, p≤0.05), visuospatial function (t=-2.84, p≤0.01), as well as a higher level of depression (t=2.87, p≤0.01) than patients who did not suffer from COVID-19. No statistical differences were found in terms of anxiety in both groups. A direct correlation was established between the level of leukocytes and cognitive functions (r=0.477, p≤0.01) and also visuospatial function (r=0.591, p≤0.05). An inverse correlation between procalcitonin level and mental status was also established (r=-0.622, p≤0.01). The conducted study proved the statistical significance of clinical-neurological, laboratory and neuropsychological indicators of patients with cerebrovascular disease infected with SARS-CoV-2.